Creep-Damage in Pressure Components Experiencing Follow-Up - Seshadri, R. (Engineering Transactions, 1989)
A simple method for estimating creep-damage in pressure components experiencing elastic or creep follow-up is presented. The theoretical formulation essentially relates the multiaxial relaxation process that exhibits follow-up to the traditional uniaxial stress-relaxation model. The resulting mixed-mode response is expressed in the generalized local stress-strain plot. The follow-up parameters are then determined by utilizing the slope of the relaxation-response in the generalized local stress-strain plot. Finally, a procedure for partitioning the accumulated fellow-up damage into Ioad-controlled and deformation-controlled contributions is discussed. The method is applied to a typical elevated-temperature piping system configuration that exhibits follow-up potential.